The Influence of Good Corporate Governance, Profitability, and Profit Growth on Company Value - Johansyah, Sheilla Amelia; Suryaputra, Verawati (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
The misalignment between the strong macro fundamentals of the Indonesian healthcare sector post-pandemic and the high volatility of the capital market. This study analyzes the influence of good corporate governance (measured by institutional ownership), profitability (measured by return on assets), and profit growth (measured by year-over-year analysis) on firm value using Tobin's Q. This quantitative research using the hypothetico-deductive method uses panel data from 28 companies during the 2022-2024 period, resulting in 84 samples, analyzed with Eviews13. The results indicate that, partially or simultaneously, the three independent variables do not significantly influence firm value, with an adjusted R^2 of only 0.47%, indicating that 99.53% of the variation in firm value is explained by factors outside the model. It is concluded that in this context of high volatility, factors such as corporate governance, profitability, and profit growth are not sufficient to explain firm value, so further research requires broader consideration of other factors and an extended period. However, findings in the Indonesian healthcare sector remain inconsistent, particularly in the post-pandemic period. Therefore, this study aims to examine the partial and simultaneous effects of good corporate governance, profitability, and profit growth on the value of healthcare sector companies on the IDX for the 2022-2024 period.